Mengasah Ekspresi dan Kecerdasan Emosional Anak Melalui Art Class di Yayasan Peduli Anak - Arisanti, Ivon; Mandalika, Dewi; Nuriana, Indra; Mardafila, Jelita (Alamtana: Jurnal Pengabdian Masyarakat UNW Mataram, 2025)
The Art Class at the Peduli Anak Foundation aims to hone children's expression and enhance their emotional intelligence through art. Through a participatory approach, children are assisted in drawing and crafting, which serve as non-verbal therapy. The results of this activity demonstrate increased self-confidence, emotional management skills, and social skills. Children become more open in expressing their feelings through artwork and demonstrate positive behavioral changes. Art class provides a safe space for children to explore their emotions, enhance creativity, and foster empathy and collaboration. This activity has proven effective in shaping children's character and supporting their psychosocial development, especially for those from less emotionally supportive backgrounds.